PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE UNTUK MENINGKATKAN KEMAMPUAN MENULIS PANTUN SISWA KELAS VII MTsN BANJAR SELATAN I KOTA BANJARMASIN - Ngatiyem, Ngatiyem (Vidya Karya Jurnal Kependidikan, 2015)
The insufficiency of studentsâ ability in writing traditional poetry learning for Grade VII students of MTsN Banjar Selatan I in Banjarmasin city has encouraged the researcher to conduct an action research study by applying the think, pair, and share type of cooperative learning model. The study was conducted in two cycle, with two meeting session for each cycle. The data collection technic used were test and observation. The result of the study has shown that: (1) the teacher activity has improved from the score rate of 4,1 (good category) in cycle I to 4,6 (very good category) in cycle II, (2) studentâs activity has improve from the score rate of 7,90 in cycle I to 11,24 in cycle II, (3) the students ability in writing traditional poetry has improved from the mark rate of 66,62 in cycle I to 80,10 in cycle II with mastery category. Therefore, it can be concluded that think, pair, and share type of cooperative learning model is effective in improving writing traditional poetry ability for grade VII students of MTsN Banjar Selatan in Banjarmasin.